CHARACTERIZATION OF XANTHOMONAS AXONOPODIS PV. PUNICAE ISOLATES FROM WESTERN MAHARASHTRA AND THEIR SENSITIVITY TO CHEMICAL TREATMENTS - K. S. RAGHUWANSHI; B. A. HUJARE; V. P. CHIMOTE; S. G. BORKAR (The Bioscan, 2013)
Bacterial blight of pomegranate caused by Xanthomonas axonopodis pv. punicae is a major biotic constraint in peninsular India. Field survey was undertaken in the major pomegranate growing regions of Western Maharashtra, which revealed the high prevalence of bacterial blight incidence in Solapur, Sangli and Nashik districts. Four different isolates of this pathogen were obtained from the highly infected plant materials collected during the field survey. X. axonopodis pv. punicae was detected from infected plant material and its identity was confirmed by morphological, physiological, hypersensitive and pathogenicity tests. Nashik isolate was most virulent. On Inter Simple Sequence Repeat (ISSR) analysis they formed separate clusters with Akkalkot-Solapur isolate being most divergent, while Deola-Nashik and Sangamner-Ahmednagar isolates were most similar. Six chemical treatments showed complete control under in vitro conditions while rest varied in their response to isolates. Complete control in all four isolates was observed with Bordeaux mixture (1%); captan (0.25%) + Copper oxychloride (0.3%), captan (0.25%) + copper hydroxide (0.3%), bromopol (500 ppm) + copper oxychloride (0.3%), streptocycline (250 ppm) + copper hydroxide (0.3%), streptocycline (500 ppm) + copper hydroxide (0.3%) during in vitro study.